MEANING OF THE TERMS AMNESTY AND PARDON IN THE MACEDONIAN CRIMINAL LAW - Simjanoska, Nada (Journal of process management and new technologies, 2017)
From antient times and on, the amnesty and the clemency respresent an act of grace, term of highest grace that provides the necessary safety valve of justice. It is expected from the amnesty and clemency to ensure that justice will became more humane despite the high inflexibility of the laws. It is expected to be taken into account the hesitation left after few verdicts, although all of the effective verdicts, in principle, are connected with the invincible legal assumption that they have been legitimate. The purpose of this research is through some examples in the Macedonian law to achieve more detailed explanations i.e. analysis of the terms amnesty and clemency. At the beginning of this study are shown the definitions of amnesty and clemency itsself, the review of the laws related to the amnesty and clemency in the Macedonian criminal law, and at the end with reference thereto to be presented the legal framework within our country, i.e. in the Macedonian criminal law and the ways which these terms can be realized in. This study is an attempt to confirm that Macedonia will keep on fulfilling the international principles on human rights, and its obligations according to the international agreements, with the aim to protect and to promote the situation of its citizens.